IMPLEMENTASI METODE BATU PIJAR DALAM PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN AKTIFITAS DAN HASIL BELAJAR SISWA SD NEGERI 47 KOTA JAMBI - Dewi Sutria (Universitas Syiah Kuala, 2019)
This research was conducted with the aim to find empirical evidence about the impact of the application of the Batu Pijar method in learning mathematics to learning activities and student achievement in learning mathematics. This research was conducted following a class action research procedure with the Kemmis and Taggart design. The subjects of this study were students of class VI C of Elementary School 47 Jambi City in the even semester of the 2018/2019 school year consisted of 30 people. The learning outcomes using the Batu Pijar method show that there was an increase in student learning activities. Positive results on student learning activities in mathematics can be seen from the tendency of increasing student learning activities in each cycle. in the first cycle (with an average of 9.33), at the time before the application of the Batu Pijar method the result was 12.4 in the first cycle and continued to increase to 13.17 in the second cycle, a good classification with an average of 14.67 in the cycle III and also with good classification with an average of 14.6 in the IV cycle.. Likewise student achievement has increased in terms of average and mastery learning. Average learning outcomes increased by 2.51% (from 79.7 to 81.7) and mastery learning increased by 11.11% (from 90% to 100%). Based on these results it can be said that the implementation of the Batu Pijar method in learning mathematics, contributes positively in increasing learning activities and student achievement in mathematics